Observations of Geomagnetic Crochet at High‐Latitudes Due To X1.5 Class Solar Flare on 3 July 2021 - S. S. Rao; Nandita Srivastava; Monti Chakraborty; Sandeep Kumar; D. Chakrabarty (Space Weather)
Abstract On 3 July 2021, an X1.5 solar flare from the National Oceanic and Atmospheric Administration solar Active Region AR12838 (24°N, 88°W) occurred at 14:18 UT, peaked at 14:29 UT, and decayed at 14:34 UT. The study of this X1.5 solar flare is significant due to its unique geomagnetic crochet feature at high latitudes and its effective signature on Earth. The study examined X‐rays, the extreme ultraviolet spectrum, ionospheric equivalent current (IEC), and geomagnetic field components. The study reveals a sudden increase in IEC during the X1.5 flare episode, forming a zonal current region and producing a geomagnetic crochet signature in geomagnetic field components at high latitudes (50°–80°N) along the 11°–26°E longitude sector during the flare peak time. All three geomagnetic field components show different sensitivity to the solar flare effect (sfe), and the amplitude and phase of the geomagnetic crochet across latitudes (for a given longitude) are consistent with the variations in the IEC. The present study is the first to appraise geomagnetic crochets of low magnitude (8–40 nT) and short duration (10–15 min) at high latitudes, particularly in the polar cusp region, during the X‐class limb flare.